INNOVATION AND REGIONAL DEVELOPMENT OF THE EUROPEAN UNION - Proniewski, Marek (Ekonomia i Prawo. Economics and Law, 2013)
The paper supports the thesis that there is an interdependence between the regional development of the European Union and variables that characterize territorial innovation. Innovation conditions the growth of the regional economy and its competitiveness on a global scale. The purpose of the analysis is to determine the groups of the level of disparities in the development of the EU regions (HDI), the clusters of regions in terms of innovation, and to examine the relationships between the level of development of the regions of European countries and the studied elements of innovation, by using statistical methods (k-means method and objective tree). The paper includes own results of calculations based on statistical data from the Eurostat databases. The results indicate regions in Europe of competitive (the highest) level of innovation and validate the thesis about the existence of the relationship between the regional development of the European Union and variables describing the innovation of the regions, particularly the expenditure on research and development, the high-tech patent applications to the EPO and the employment in science and technology.